دور البرامج التدريبية في تعزيز كفاءة أداء الموارد البشرية العاملة في المديرية العامة للدفاع المدني الأردني - Ibrahim Muhammad Mahmud Hatamilah; ابراهيم محمد محمود حتاملة (Universiti Sains Islam Malaysia, 2024)
Matric : 4130084 (FKP)